Penerapan Hukum Partisipasi Publik dalam Keberkelanjutan Pembentukan Undang-Undang Periode 2019-2024 - Chelvin Rachello; Fakhris Lutfianto Hapsoro (LPPM Iblam School of Law, 2026)
This study examines public participation in the implementation of the carry over mechanism in Indonesia’s legislative process during the 2019–2024 period. The sustainability mechanism aims to ensure continuity and efficiency by allowing unfinished bills to be continued across parliamentary terms. Using a normative juridical approach, this research analyzes statutory regulations, Constitutional Court decisions, and legal literature. The findings indicate that although sustanaibility supports legislative continuity, its implementation has been ineffective due to frequent changes in the National Legislation Program and political dynamics within the legislature. Moreover, public participation in sustainability legislation remains largely procedural and fails to meet the standards of meaning participation as mandated by law and Constitutional Court jurisprudence.